Diagnostic Injection Laryngoplasty Predicts Success of Type I Laryngeal Cleft Repair: Results of Pilot Study. (23rd August 2013) - Skinner, Margaret L.; Mavrothalassitis, Orestes; Ishman, Stacey L.; Au Yeung, Karla J.; Collaco, J. Michael; Lefton‐Greif, Maureen
Abstract : Objectives: A pilot study to determine the effectiveness of injection laryngoplasty (IL) as a predictor for success of subsequent endoscopic laryngeal cleft repair (ELCR). Study Design: Case series with chart review. Setting: Tertiary care academic hospital. Methods: Retrospective analysis of children with type I laryngeal clefts who underwent IL and/or ELCR from September 2009 to January 2013. Results: Thirty‐six patients underwent IL with or without subsequent ELCR, and 11 underwent ELCR alone. Of those who underwent isolated ELCR, 8/11 (72.7%) had complete resolution of presenting symptoms. Of those who underwent IL, 29/36 (81%) had adequate follow‐up and 21/29 (72.4%) experienced compete resolution of presenting symptoms, similar to those undergoing ELCR ( P = 0.679). Fourteen with complete response and 1 with partial response to IL underwent subsequent ELCR with adequate follow‐up. In all cases, response to ELCR was predicted by response to IL; 14 experienced complete resolution and 1 had partial resolution of presenting symptoms. While the rate of full resolution of symptoms following ELCR was better in the children undergoing previous successful diagnostic IL, it did not reach statistical significance ( P = 0.072) due to the limited sample size. Conclusions: Diagnostic IL is an effective indicator for successful ELCR. This suggests that IL may be a useful diagnostic method to determine the degree of pathology presented by a type I laryngeal cleft in symptomatic patients and to predict the degree of success of subsequent ELCR. Future studies employing a larger sample size are recommended to confirm this relationship.